2015
DOI: 10.1002/ccd.25819
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical features and management of bioresorbable vascular scaffolds failure: A case series from the GHOST registry

Abstract: The Absorb bioresorbable vascular scaffold (Absorb BVS, Abbott Vascular, Santa Clara, California) promises to address some of the residual shortcomings of existing metallic stents, such as late events induced by permanent caging of the coronary vessel. Scaffold restenosis (ScR) of BVS has been poorly described so far and treatment strategies for this event remain to be codified. We report on a case series of 14 lesions in 12 patients presenting with ScR and discuss their anatomical features and management stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Most importantly, the ACR data significantly added information to the findings of the prior OCT imaging without co‐registration, which had already affected PCI strategy (Table ). The advantages of this novel coregistration between different coronary imaging technologies became most evident in complex coronary artery lesions prone to adverse events after PCI , for example, in diffusely diseased vessel segments or when precise stent deployment may be hampered due to missing anatomical landmarks. In such cases, ACR provides incremental imaging information, which may translate into improved procedural outcomes, especially for the use of bioresorbable devices .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the ACR data significantly added information to the findings of the prior OCT imaging without co‐registration, which had already affected PCI strategy (Table ). The advantages of this novel coregistration between different coronary imaging technologies became most evident in complex coronary artery lesions prone to adverse events after PCI , for example, in diffusely diseased vessel segments or when precise stent deployment may be hampered due to missing anatomical landmarks. In such cases, ACR provides incremental imaging information, which may translate into improved procedural outcomes, especially for the use of bioresorbable devices .…”
Section: Discussionmentioning
confidence: 99%
“…When BVS restenosis occurs after 6 months or later, the biodegradation phase has already started and the scaffold has lost its properties, so simple dilatation has unknown outcomes. 27 In our registry, operators decided to treat scaffold restenosis with DEB rather than with DES, in case of focal restenosis pattern, irrespective of the presentation time, to avoid a further stent implantation in a vessel already treated with ≥1 stent and the BVS that has not completed the absorption.…”
Section: Downloaded From Bioresorbable Scaffold For In-stent Restenosmentioning
confidence: 99%
“…Limited data are available in the literature on this topic (14,15). IScaR may be attributed to multiple factors which include: geographical miss (edge effect) defined as failure of the device to appropriately scaffold a balloon-injured vessel or to fully cover the lesion, scaffold underexpansion, scaffold gap (missing overlap of several mm), uneven scaffold implantation in tight stenosis, small target vessel diameter (<2 mm) (strut overcrowding), delayed scaffold resorption, excessive neointimal proliferation, neoatherosclerosis and resistance to antiproliferative drugs (16,17). Some authors have found that early restenosis (<6 months) tended to be focal, mostly affecting the BVS edges, and showed a homogeneous appearance tissue.…”
Section: Clinical Datamentioning
confidence: 99%
“…Different coronary devices were used in the management of this issue. In a case series from the GHOST-EU trial where BVS failure was caused by scaffold restenosis, percutaneous balloon angioplasty, drug-coated balloons (DCB), DES and BVS implantation were used in 2 (14%), 6 (43%), 5 (36%), and 1 (7%) case, respectively (16).…”
Section: Treatment Of Bvs Failurementioning
confidence: 99%